Collaborative Learning, Gender Groupings and Mathematics Performance - Lim, Edgar Julius A. (ASEAN Journal of Education, 2016)
This study was conducted to find how students perform in class if they work in groups. It also wanted to find out which gender groupings of students facilitate comfortable studies and better academic results. An experimental research design was utilized where the subjects were randomly assigned. The subjects in this study comprised 9 groups: three allmale groups, three all-female groups, and three mixed groups. Using ANOVA, data analysis revealed that the subjects’ formative tests mean scores had no significant difference which implies that if subjects were working alone, they obtained more or less similar results. The collaborative learning treatment, where the subjects worked in different gender groups, showed that there was a significant difference in their performance. Specifically, all-female groups obtained the highest mean score followed by mixed groups; this implies that if subjects work with others whom they are comfortable with, their results increase. In the math achievement test, which was taken individually, a significant difference in the mean scores obtained was observed; this level of improvement in their learning which could be attributed to the groups they worked with and learned the concepts with.